SQUAMUS CELL CARCINOMA lN PERSISTENCE OF THYROGLOSSAL DUCT CYST - Paule, P. Navarro (2006)
We describe the case of on squamous cell carcinoma in thyroglossal Duct cyst in a fifty-four years old patient showing persistance of the thyroglossal duct.We describe the diognosis methods followed, the treatment carried out and the present status of the illness.It is an excepcion that the thyroglossal duct cyst becomes malignant, as this only happens in o 1% of the cases, most of the times they ore papillary carcinomas and anaplastics carcinomas.